2022
DOI: 10.1007/s11032-022-01277-w
|View full text |Cite
|
Sign up to set email alerts
|

Pyramiding of genes for grain protein content, grain quality, and rust resistance in eleven Indian bread wheat cultivars: a multi-institutional effort

Abstract: Improvement of grain protein content (GPC), loaf volume and resistance to rusts was achieved in 11 Indian wheat cultivars that are widely grown in four different agro-climatic zones of India. This involved use of marker-assisted backcrossing (MABC) for introgression and pyramiding of the following genes:(i) the high GPC gene Gpc-B1; (ii) HMW glutenin subunits 5 + 10 at Glu-D1 loci, and (iii) rust resistance genes, Yr36, Yr15, Lr24 and Sr24. GPC was improved by 0.8-3.3%, although high GPC was generally associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…But in such cases, the number of effective tillers and grins per spike is adjusted to compensate for the yield. A similar result is observed in some previously conducted studies in the wheat germaplasm with Indian origin ( Vishwakarma et al, 2014 , 2016 ; Gupta et al, 2022 ). The present study remarkably identified that the acceptable level of stability and top-performing potential in one genotype for a character are not the same in other characters.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…But in such cases, the number of effective tillers and grins per spike is adjusted to compensate for the yield. A similar result is observed in some previously conducted studies in the wheat germaplasm with Indian origin ( Vishwakarma et al, 2014 , 2016 ; Gupta et al, 2022 ). The present study remarkably identified that the acceptable level of stability and top-performing potential in one genotype for a character are not the same in other characters.…”
Section: Discussionsupporting
confidence: 91%
“…In many studies, grain protein content (GPC) has been observed to be the most important factor influencing end-use quality and thus has a significant impact on the economic importance of wheat ( Saini et al, 2020 ). As a direct consequence, GPC improvement in wheat has become a top priority in wheat breeding research projects, particularly for those looking at improvement in nutritional quality ( Shewry, 2009 ; Gudi et al, 2022 ), especially for the people who cannot afford supplements to fulfill their daily recommended intake of protein. Since a negative association is generally observed between GPC and grain yield, developing an elite wheat cultivar having higher yield potential and GPC is considered a major challenge, taking the current growing rate of food requirements into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…India has been producing sufficient wheat to contribute towards food security in the recent past but is still unable to cater to the undernourishment and malnutrition issues, especially for the masses. However, a decline in the undernourished population was witnessed, although a reverse trend started again after 2015, so that currently 9%–11% of the world’s population suffers from undernourishment/malnutrition, and this is likely to increase further (by∼0.8%–1.0%) by 2030 when >850 million people are predicted to suffer with hunger and undernourishment/malnutrition ( Purugganan and Jackson 2021 ; Gupta et al, 2022 ). The wheat crop deserves major attention as it is the second most important crop after maize in terms of staple food and the second most important crop after rice in terms of food and nutritional security.…”
Section: Discussionmentioning
confidence: 99%
“…The wheat crop deserves major attention as it is the second most important crop after maize in terms of staple food and the second most important crop after rice in terms of food and nutritional security. Many efforts are underway to combine different subcomponents of nutritional quality in wheat, particularly in terms of grain protein content (GPC), iron content, zinc content, and antioxidant content ( Gupta et al, 2020 ; Gupta et al, 2021 ; Gupta et al, 2022 ). A novel component of biofortification in wheat other than enhancing iron or zinc content is the enhancement of carotenoid pigments in the mature grain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation